Hippocampal Neurophysiologic Changes after Mild Traumatic Brain Injury and Potential Neuromodulation Treatment Approaches - Girgis, Fady; Pace, Jonathan; Sweet, Jennifer; Miller, Jonathan P. (Frontiers in Systems Neuroscience, 2016)
Traumatic brain injury (TBI) is the leading cause of death and disability in individuals below age 45, and 5 million Americans live with chronic disability as a result. Mild TBI (mTBI), defined as TBI in the absence of major imaging or histopathological defects, is responsible for a majority of cases. Despite the lack of overt morphological defects, victims of mTBI frequently suffer lasting cognitive deficits, emotional difficulties, and behavioral disturbances. There is increasing evidence that cognitive dysfunction is related to subtle physiological changes that occur within several brain structures and these impact both the phenotype of deficits observed and subsequent recovery. Therapeutic modulation of physiological activity by means of medications commonly used for other indications or brain stimulation may represent novel treatment approaches. This review summarizes the present body of knowledge regarding neurophysiologic changes that occur after mTBI, as well as potential targets for therapeutic modulation of neurologic activity.